Combination of transsphenoidal endoscopic surgery and presurgical somatostatin analogs in thyrotropin (TSH)-secreting pituitary adenomas: Treatment outcome and long-term remission at a single pituitary center - Liu, Jie; Yang, Yamei; Duan, Lian; Chai, Xiaofeng; Zhu, Huijuan; Deng, Kan; Lian, Xiaolan; Yao, Yong (Frontiers in Endocrinology, 2022)
Background: Thyrotropin (TSH)-secreting pituitary adenomas (TSHomas) account for an extremely rare group of pituitary adenomas. Few studies examined the sensitivity and efficacy of pre-surgical Somatostatin analogs (SSA) and described the long-term remission under such treatment modality. The aim of the present study was to assess efficacy of pre-surgical SSA treatment and long-term remission after surgery. Methods: A retrospective cohort of 65 TSHoma patients who received endoscopic transsphenoidal pituitary surgery between 2011 and 2020 in a single pituitary center in China was established. Data were analyzed for sex difference and different types of SSA and ultimately explore a hormonal cutoff for remission prediction. Results: TSHomas had a predominant female preference in this cohort (43 females vs 22 males). Baseline FT3 was higher in males [7.543±2.407 vs 5.58(4.99,6.58), p=0.019], which was consistent with its longer diagnosis time and larger tumor volume. Median medication time for hormonal control was 2.5 days for short acting SSA and 4.0 weeks for long-term SSA. Patients with long acting SSA had shrinked tumor maximum diameter at a median of 1.0(-1.6,4.925) mm. Only 10 patients (15.38%) were not in complete remission among whom 8 patients were not en-bloc resected and 2 patients were tumor recurrent after 81.6 and 10.7 months of complete removal. Post-surgical thyroid hormones (within one week) of TSH<0.094μIU/mL was identified as cutoff for remission using ROC curve. Conclusions: Combination of endoscopic transphenoidal surgery and pre-surgical SSA TSHomas contributed a higher long-term remission for TSHsomas.